2009
DOI: 10.1126/scisignal.2000546
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Protein Domains as Functional Units of Cellular Evolution

Abstract: Modular protein domains are functional units that can be modified through the acquisition of new intrinsic activities or by the formation of novel domain combinations, thereby contributing to the evolution of proteins with new biological properties. Here, we assign proteins to groups with related domain compositions and functional properties, termed "domain clubs," which we use to compare multiple eukaryotic proteomes. This analysis shows that different domain types can take distinct evolutionary trajectories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 72 publications
(92 reference statements)
5
130
0
1
Order By: Relevance
“…Second, both RIN3 and CD2AP were among 21 proteins pulled down from kidney cells by the SH3-5/6 domains of the large adaptor protein TUBA (51). TUBA contains six SH3 domains and has guanine nucleotide exchange factor activity toward CDC42.…”
Section: Discussionmentioning
confidence: 99%
“…Second, both RIN3 and CD2AP were among 21 proteins pulled down from kidney cells by the SH3-5/6 domains of the large adaptor protein TUBA (51). TUBA contains six SH3 domains and has guanine nucleotide exchange factor activity toward CDC42.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the pTyr-binding SH2 domains, all 121 human family members are predicted to adopt a general structural fold consisting of a large seven-strand b-sheet flanked by two a-helices, and indeed there are solved structures for more than 60 SH2 domain family members [68,69]. Humans and yeast share only one related protein that possesses a sequence corresponding to an SH2 domain (Supt6H/ Spt6), and this is the only evident SH2-containing protein in yeast [53]. Structural analysis has shown that yeast Spt6 actually has two rigidly linked tandem SH2 domains, of which only the N-terminal domain (SH2N) was identified by sequence [70,71].…”
Section: The Evolutionary Trajectories Of Kinases Phosphatases and Pmentioning
confidence: 99%
“…We have proposed that domains such as 14-3-3 that are never normally joined to other modules are maintained in this isolated state owing to their central role in numerous aspects of cellular regulation and organization, which might be corrupted by incorporation into a larger polypeptide [53]. An alternative possibility is that the joining of a 14-3-3 domain to another sequence might interfere with its structure and function on biophysical grounds.…”
Section: -3-3 Proteins: the Exception That Proves The Rule?mentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing of higher eukaryote genomes revealed that many protein coding genes bear hallmarks of hybridization and recombination events [2]. Many such evolutionary cassettes fold into sizable, distinct units that can be easily recognized in the three-dimensional structures [30]. Other recognizable and frequent elements are short motifs.…”
Section: Introductionmentioning
confidence: 99%